(untitled) (Psychology Travelogs, 2023)
The article presents the results of a study of the nature of the relationship between students’ preferences for distance or traditional forms of learning and their alienation from it and emotional burnout, taking into account the subjective assessment of learning progress, self-control and academic control. It is noted that preferences in the choice of distance or traditional forms of education reflect the motivational, semantic and regulatory features of students’ learning activities. The preference for distance learning by students who experience alienation from learning and emotional burnout, as established in the study, may mean that it conceals the desire to find a new, more acceptable format that would better meet their needs and characteristics caused by the difficulties of adapting to the traditional format. In the practice of using distance studying, it is necessary to take into account that the advantage of this form is more inherent in students who experience negative motivational and semantic states in studying, combined with relatively low formation of regulatory qualities: self-control and academic control. It is crucial to understand the role and place of self-control in distance studying when designing such courses. For those who prefer this form of studying, it is advisable to provide special measures to help students maintain and develop self-control. For most students, the transition to distance studying in higher education seems to be an unattractive alternative to traditional studying, which threatens the quality of education, while blended studying is assessed much more positively. This gives grounds to state that in situations like the current one in Ukraine, which require a choice between distance and blended studying, the use of the second form in higher education seems more justified.